Professional nurses’ perspectives on the implementation of integrated chronic disease management model - Avhaathu S. Dagume-Ndou; Thanyani G. Lumadi (Curationis)
Background: The integrated chronic disease management (ICDM) model is seen to be a promising strategy as it is gaining global acceptance as an approach to enhance healthcare delivery.